2016
DOI: 10.1007/s11244-016-0587-x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Phosphorus Exposure on a Natural-Gas-Oxidation Catalyst

Abstract: Phosphorus is found to have a deactivating effect on the catalytic activity of the studied natural-gas-oxidation catalyst. Accelerated laboratory-scale phosphorus treatment was done to the PtPd/Al 2 O 3 natural gas oxidation catalyst. The effect of phosphorus after low (0.065 M) and high (0.13 M) phosphorus concentration treatments was studied by using an inductively coupled plasma optical emission spectroscopy, N 2 physisorption, X-ray diffraction, field emission scanning electron microscopy, transmission ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…From the XPS spectra shown in Figure 5 (left column), we found that phosphorus is present in the inlet sample of the engine bench aged oxidation catalyst in two different forms, as phosphate (135 eV) and oxidized phosphorus (likely at 138 eV) [39]. P 4 O 10 , also known as phosphate glass, covers the surface of the sample in a non-selective way, while the phosphates could form bonds with the alumina support [40,41]. For the outlet sample of the engine bench aged oxidation catalyst, mainly phosphate is found, and this is most likely due to P 4 O 10 sticking to the first surface it comes in contact with, which is the inlet of the oxidation catalyst.…”
Section: Docrefmentioning
confidence: 99%
“…From the XPS spectra shown in Figure 5 (left column), we found that phosphorus is present in the inlet sample of the engine bench aged oxidation catalyst in two different forms, as phosphate (135 eV) and oxidized phosphorus (likely at 138 eV) [39]. P 4 O 10 , also known as phosphate glass, covers the surface of the sample in a non-selective way, while the phosphates could form bonds with the alumina support [40,41]. For the outlet sample of the engine bench aged oxidation catalyst, mainly phosphate is found, and this is most likely due to P 4 O 10 sticking to the first surface it comes in contact with, which is the inlet of the oxidation catalyst.…”
Section: Docrefmentioning
confidence: 99%
“…Considering industrial applications, adding additives to catalysts is the easiest way to achieve the goal; therefore, it is very necessary to study the role of additives in catalysts. So far, various additives have been reported, such as metallic [ 7 , 8 , 9 ] and non-metallic additives [ 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are many studies on the catalytic activity of propane and CH 4 with the addition of phosphorus to Pd/Al 2 O 3 [ 19 , 20 , 21 ]. It has been proven that the addition of P can generate Brønsted acid sites on the Al 2 O 3 surface, which is mainly related to the generation of P-OH groups and the redistribution of oxygen and aluminum atoms [ 13 , 19 , 20 ]. The introduction of P results in defects and vacancy in Al 2 O 3 , creating a coordination of unsaturated penta-coordinated aluminum sites.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, most of the current research studies on phosphorus poisoning were not carried out under operational conditions (e.g., dynamic air−fuel ratio and longterm thermal aging). 18 This may fail to help understand the behavior and mechanism of phosphorus poisoning. To date, few works about phosphorus tolerance under NGV operational conditions were reported.…”
Section: Introductionmentioning
confidence: 99%
“…However, the real composition of the deposited phosphorus species was not specified. Besides, most of the current research studies on phosphorus poisoning were not carried out under operational conditions (e.g., dynamic air–fuel ratio and long-term thermal aging) . This may fail to help understand the behavior and mechanism of phosphorus poisoning.…”
Section: Introductionmentioning
confidence: 99%